A Randomized Clinical Trial of Infrared Coagulation Ablation Versus Active Monitoring of Intra-anal High-grade Dysplasia in Adults With Human Immunodeficiency Virus Infection: An AIDS Malignancy Consortium Trial. (27th July 2018) - Goldstone, Stephen E; Lensing, Shelly Y; Stier, Elizabeth A; Darragh, Teresa; Lee, Jeannette Y; van Zante, Annemieke; Jay, Naomi; Berry-Lawhorn, J Michael; Cranston, Ross D; Mitsuyasu, Ronald; Aboulafia, David; Palefsky, Joel M; et al.
Abstract: Background: Anal high-grade squamous intraepithelial lesions (HSILs) ablation may reduce the incidence of invasive cancer, but few data exist on treatment efficacy and natural regression without treatment. Methods: An open-label, randomized, multisite clinical trial of human immunodeficiency virus (HIV)–infected adults aged ≥27 years with 1–3 biopsy-proven anal HSILs (index HSILs) without prior history of HSIL treatment with infrared coagulation (IRC). Participants were randomized 1:1 to HSIL ablation with IRC (treatment) or no treatment (active monitoring [AM]). Participants were followed every 3 months with high-resolution anoscopy. Treatment participants underwent anal biopsies of suspected new or recurrent HSILs. The AM participants underwent biopsies only at month 12. The primary end point was complete clearance of index HSIL at month 12. Results: We randomized 120 participants. Complete index HSIL clearance occurred more frequently in the treatment group than in the AM (62% vs 30%; risk difference, 32%; 95% confidence interval [CI], 13%–48%; P < .001). Complete or partial clearance (clearance of ≥1 index HSIL) occurred more commonly in the treatment group (82% vs 47%; risk difference, 35%; 95% CI, 16%–50%; P < .001). Having a single index lesion, compared with having 2–3 lesions, was significantly associated with complete clearance (relative risk, 1.96; 95% CI, 1.22–3.10). The most common adverse events related to treatment were mild or moderate anal pain and bleeding. No serious adverse events were deemed related to treatment or study participation. Conclusion: IRC ablation of anal HSILs results in more clearance of HSILs than observation alone. Abstract : Ablation of anal canal high-grade squamous intraepithelial lesions (HSILs) is more likely to result in a complete or partial resolution of HSILs than monitoring alone. Spontaneous HSIL regression occurred, and a 1-year delay in treatment did not affect ultimate outcomes.